FAKTOR-FAKTOR YANG MEMPENGARUHI VOLUNTARY DISCLOSURE PERUSAHAAN GO PUBLIC - Tulus - Prijanto; Yuni Pristiwati Noer Widianingsih (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2012)
ABSTRACT This paper is to investigate factors which influence voluntary disclosure level of annual report manufacture companies listed on the Indonesian Stock Exchange (IDX). Factors are leverage, percents of public stocks and age of company. The sample consist 86 manufacture companies are published annual report of December 31, 2008. The result shows are percents of public stocks and age of company have effect significant of voluntary disclosure level. However leverage doesn’t effect on the voluntary disclosure level. Keywords: voluntary disclosure, leverage, percents of public stocks and age of company.